Analysis of Factors Influencing Students’ Decisions in Choosing A Private College in Yogyakarta: University Decision - Riefda Aulia Putri (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
This research aims to examine and analyze the influence of several factors on university selection, such as university location, perceptions about the university, graduate employability, tuition fees, academic quality, and university brand. The analysis carried out will provide an in-depth understanding of how significant the influence of each of these factors is in influencing prospective students’ decisions in choosing their university. This study uses a descriptive approach to observe and analyze the relationships between variables. The purposive sampling method was used to select respondents who met the criteria, with questionnaires distributed via Google Mail to new UII students class of 2023 to facilitate accurate and efficient online data collection. The results of this research show that location, perception of the university, and academic quality do not influence the choice of university and the ones that do are the employability of graduates, tuition fees, and brand.